Analisis Yuridis Perbuatan Melawan Hukum terhadap Perubahan Secara Sepihak dalam Sengketa Perjanjian Bangun bagi yang Dilegalisasi oleh Notaris : Studi Putusan No.550/Pdt.G/2024/Pn Medan - difa mutia dara aflah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the juridical analysis of unlawful acts arising from unilateral changes in a build-sharing agreement dispute legalized by a notary based on Decision Number 550/Pdt.G/2024/PN Medan. The issue arises from inconsistencies between the parties’ initial agreement and its implementation, particularly the emergence of a deed of rights release transferring land ownership to the developer, causing losses to the landowner. This study aims to analyze the fulfillment of the elements of unlawful acts, the legal consequences, legal protection for the injured party, and the judge’s legal considerations. This research employs a normative legal method with statutory, conceptual, and case approaches through qualitative library research. The findings indicate that unilateral changes fulfill the elements of unlawful acts under Article 1365 of the Indonesian Civil Code. Notary legalization potentially violates the principle of prudence, causes material losses, and was judicially classified as an unlawful act due to violations of consensualism, good faith, and contractual justice principles.